Radiofrequency ablation compared with repeat hepatectomy for patients with recurrent hepatocellular carcinoma: A meta-analysis - Yi-gang Zhang; Zhi-duan Xu; Hong-xiang Yin; Xiang-yang Zhao; Bo-wen Jiang; Yong Gao; Yi Tan (Journal of Radiation Research and Applied Sciences, 2022)
The therapy of recurrent hepatocellular carcinoma (RHCC) remains poorly defined. Repeat hepatectomy (RH) and radiofrequency ablation (RFA) have offered as alternative therapy choices. Our study aims to assess survival benefits of RFA versus reresection for RHCC after resection. The electronic databases were used in order to explore the researches analyzing the efficacy of RH vs. RFA in treating RHCC updated to June 2020. After strict evaluation on quality, the interested results were extracted from articles. Totally, a total of 11 publications involving 1515 subjects were included, with 645 conducted RH and 870 taking RHA. We found that RH was associated with better 3-year OS (OR = 1.58, 95% CI = 1.22–2.05, P = 0.0005), while no difference with 1-year (OR = 1.03, 95% CI = 0.07–1.51, P = 0.90) or 5-year OS (OR = 1.66, 95% CI = 0.88–3.14, P = 0.12) in comparison with RFA for RHCC. In terms of DFS, RH was associated with better 3-year DFS (OR = 1.51, 95% CI = 1.11–2.06, P = 0.009) and 5-year DFS (OR = 1.54, 95% CI = 1.14–2.09, P = 0.005) than RFA. Moreover, RH had more morbidity compared with patients who underwent RFA for RHCC patients (OR = 5.61, 95% CI = 3.02–10.42, P < 0.00001). In conclusion, RH achieves better disease-free survival but with higher morbidity for RHCC than RFA. More researches are clearly required to further strengthen quality of results and standardize the method.